8th Grade Math
posted by Cassidy on .
5/2t  t = 3 + 3/2t
I'm having a hard time to solve this problem >.<

cancel out the denominator by multiplying by greatest common factor so 2.
2(5/2tt)=2(3+3/2t)
so now equation is 5t2t=6+3t
then solve. 3t=6+3t
you should get no solution 
I don't understand....

Anon failed to notice that t is also in the denominator.
Multiply both sides by 2t.
5  2t^2 = 6t + 3
Combine like terms.
2  2t^2 6t = 0
Multiply by 1.
2t^2 + 6t  2 = 0
I also get no solution, but at least my equation is correct. 
Anon is correct.
3t=6+3t
When we subtract 3t from both sides of the equation, we no longer have an equation. 0 = t is meaningless; therefore this problem has no solution.